Development of new methods for determining the distribution of steel fibres in the hardened steel fibre reinforced concrete – possibilities of production and verification of test specimens - Anton, Ondřej; Komárková, Tereza; Láník, Jaromír; Heřmánková, Věra (IOP Publishing, 2018)
Many research teams currently deal with the issue of determining the distribution of steel fibres in the hardened steel fibre reinforced concrete, both in terms of fibre concentration, and in terms of homogeneity of fibre distribution in the concrete. The basic element in the development of new non-destructive methods is the development of new principles and devices on adequate test specimens, in which precise spacial distribution of fibres, including the orientation of individual fibres, would be quite evident. The paper presents two technologically completely different possibilitites of dealing with this issue. X-ray radiography is a traditional and long-established method, but in the field of construction, the authors' workplace is one of the few in the Czech Republic able to use it. The method of creating transparent specimens is completely unique, as it has been developed and is used only at the authors' workplace.

Many research teams currently deal with the issue of determining the distribution of steel fibres in the hardened steel fibre reinforced concrete, both in terms of fibre concentration, and in terms of homogeneity of fibre distribution in the concrete. The basic element in the development of new non-destructive methods is the development of new principles and devices on adequate test specimens, in which precise spacial distribution of fibres, including the orientation of individual fibres, would be quite evident. The paper presents two technologically completely different possibilitites of dealing with this issue. X-ray radiography is a traditional and long-established method, but in the field of construction, the authors' workplace is one of the few in the Czech Republic able to use it. The method of creating transparent specimens is completely unique, as it has been developed and is used only at the authors' workplace.
Development of new methods for determining the distribution of steel fibres in the hardened steel fibre reinforced concrete – possibilities of production and verification of test specimens
Keywords: distribution of steel fibres; fibre concentration; homogeneity of fibre distribution in the concrete; distribution of steel fibres; fibre concentration; homogeneity of fibre distribution in the concrete